Long-Term Effects of Extended Unemployment Benefits for Older Workers - Tomi Kyyrä; Hanna Pesola (Institute of Labor Economics (IZA), 2017)
This paper examines the long-term effects of extended unemployment benefits that older unemployed can collect until retirement in Finland. We consider a reform that increased the age threshold of this scheme from 55 to 57 for people born in 1950 or later. Our regression discontinuity estimates show that postponing eligibility by two years increased employment over the remaining working career by seven months. Despite the corresponding reduction in unemployment, we find no evidence of significant effects on mortality or receipt of disability and sickness benefits, nor on the spouse's labor supply. We also compute the fiscal impact of the reform taking into account income taxes and social security contributions paid and benefits received. The reform increased net income transfers by 15,000 Euros over the 10-year period for an average individual.
Keywords: J26; J63; J64; J65; 330; early retirement; unemployment insurance; layoffs